The Concepts of Fikr and Żikr In Qs Ali Imran 190–191 As an Epistemological Foundation For The Integration of Science and Religion - Naili Agustin (Yayasan Insan Cendekia Nusantara, 2026)
Research Background: This article aims to compare classical and contemporary exegetical perspectives, identify the characteristics of ulūl albāb, and reconstruct the concepts of fikr and dhikr as complementary modes of knowledge. This study examines the interpretation of Q.S. Ali Imran verses 190–191 to explore an epistemological foundation for integrating science and religion. Methods: This study employs a qualitative library research design. Data were collected from classical and contemporary Qur’anic commentaries and scholarly literature on the integration of science and religion. The data were analyzed using content analysis and comparative interpretation. Key Findings: The results indicate that classical exegetes primarily emphasize theological and textual dimensions, whereas contemporary scholars extend the interpretation toward scientific, philosophical, and contextual perspectives. The study formulates an Integrative Epistemology Model of Fikr–Dhikr, consisting of three interconnected stages: fikr as rational inquiry, dhikr as reflective contemplation grounded in divine awareness, and i‘tirāf as ethical recognition that all knowledge ultimately originates from Allah. This model demonstrates that science and religion are mutually reinforcing rather than contradictory. Contribution: This study offers a conceptual framework for advancing science–religion integration, enriching Islamic educational philosophy, and supporting the development of ethical, spiritually grounded, and environmentally responsible scientific knowledge. Conclusion: Q.S. Ali Imran verses 190–191 provide a comprehensive epistemological framework that harmonizes reason, spirituality, and ethics in the pursuit of knowledge. The integration of fikr and dhikr encourages scientific inquiry that remains grounded in moral and spiritual responsibility.